Correction to: Congenital Anomalies of Kidney and Urinary Tract in a Dissected Cadaver: Case Report - Mohammad Hassan Sakhaie; Marziyeh Pooladi; Soheila Madadi; Yusef Abbasi (Journal of Mazandaran University of Medical Sciences, 2023)
Correction to: Congenital Anomalies of Kidney and Urinary Tract in a Dissected Cadaver: Case Report